State of the art on Authentic Materials and Listening Comprehension in Colombia (2022)
The present study shows the results of a literature review conducted to know about the state of the art of the use of authentic materials for listening comprehension in the Colombian context. The study set out to find the main trends concerning the use of such materials and opportunities to find areas for further research. The methodology used for the review was qualitative and the corpus gathered was analyzed by creating codes and categories about the emerging themes. The analysis revealed that teacher-researchers have found beneficial the use of authentic materials for listening comprehension. Also, this has been a recurrent topic studied by pre-service teachers for their undergraduate thesis projects with diverse audiences, especially during the last five years. In most of the studies considered the teacher-researchers have framed their work on listening comprehension within a pre-, while, and post-stage cycle. The methodology preferred in these studies has been action research. Given the benefits showed by the use of authentic materials for listening comprehension, it is worth finding ways to widespread this practice as pedagogical strategy among a wider audience of practitioners and not only for those in researching contexts.